Community policing and stock theft in selected rural areas of the Mpumalanga province of South Africa - Masuku, Sandile Clement; Motlalekgosi, Hendrick Puleng (Technium Social Sciences Journal, 2021)
A slight decrease in stock theft in many provinces in South Africa must be commended irrespective of the reasons behind the decrease because it is a step in the right direction. However, an increase in stock theft in the Mpumalanga province of South Africa is a cause for concern and must be handled with urgency. This paper examines the extent to which the community is involved in the fight against stock theft in the rural areas of the Mpumalanga province of South Africa. The study employed a qualitative research approach that used semi-structured in-depth interviews to collect data. The sample consisted of 22 participants selected through purposive sampling, who included farmers, herdsmen, Community Police Forum members, and community leaders. The study found that the community in the rural areas of Mpumalanga is not involved in the fight against stock theft and that this could mainly be attributed to the poor relationship between the South African Police Service and the community. It was also found that poverty and unemployment are the main contributing factors to increased stock theft in the rural areas of the Dr Pixley Ka Isaka Seme Local Municipality in Mpumalanga.